2015
DOI: 10.1161/circresaha.116.302752
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Cardiomyocyte Differentiation

Abstract: The heart is the first organ to form during embryonic development. Given the complex nature of cardiac differentiation and morphogenesis, it is not surprising that some form of congenital heart disease is present in approximately one percent of newborns. The molecular determinants of heart development have received much attention over the past several decades. This has been driven in large part by an interest in understanding the etiology of congenital heart disease coupled with the potential of utilizing know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 161 publications
(176 reference statements)
3
159
0
4
Order By: Relevance
“…In accord, more than 60 genes have been linked to ventricular noncompaction in human and mouse studies (Paige et al, 2015; Towbin et al, 2015; Wilsbacher and McNally, 2016). Disruption of endocardial and myocardial Notch signaling pathways after the onset of compaction leads to ventricular noncompaction, but in contrast to cardiomyocyte-specific S1pr1 deletion, these mutants display increased proliferation especially within the trabecular myocardium (D'Amato et al, 2016; Luxán et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accord, more than 60 genes have been linked to ventricular noncompaction in human and mouse studies (Paige et al, 2015; Towbin et al, 2015; Wilsbacher and McNally, 2016). Disruption of endocardial and myocardial Notch signaling pathways after the onset of compaction leads to ventricular noncompaction, but in contrast to cardiomyocyte-specific S1pr1 deletion, these mutants display increased proliferation especially within the trabecular myocardium (D'Amato et al, 2016; Luxán et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of either trabeculation or compaction has important consequences; failure to undergo trabeculation results in growth arrest and embryonic lethality, while defective compaction results in left ventricular non-compaction cardiomyopathy. To date the molecular mechanisms that regulate the proliferation and differentiation required for trabeculation and compaction remain incompletely understood (Paige et al, 2015; Towbin et al, 2015; Wilsbacher and McNally, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Factors explaining the remaining transcriptional variability include varying activity of enhancers 43 and transcription factors. 44 This tight link of chromatin state and transcriptional activity can only be uncovered in cell-type-specific data sets.…”
Section: Discussionmentioning
confidence: 99%
“…The first wave of cardiomyocyte precursors forms a crescent near the head folds that subsequently fuses at the midline to form the primitive heart tube (Buckingham et al, 2005). As the heart tube forms, de novo cardiomyocyte creation occurs both from the differentiation of these precursors and from a second heart field in the pharyngeal mesoderm (Kelly et al, 2001;Mjaatvedt et al, 2001;Waldo et al, 2001; reviewed by Kelly et al, 2014;Paige et al, 2015). Multiple studies in chick have revealed little evidence for cardiomyocyte division occurring during these early stages (Sissman, 1966;van den Berg et al, 2009).…”
Section: Early Cardiogenesismentioning
confidence: 99%